2018
DOI: 10.22336/rjo.2018.19
|View full text |Cite
|
Sign up to set email alerts
|

Phacoemulsification in adult patients with post-uveitis complicated cataract

Abstract: Objective: To evaluate the difficulties, complications and outcome of cataract surgery in patients with complicated cataract after anterior uveitis. Methods: A retrospective study on 37 patients who suffered phacoemulsification surgery for post-uveitis complicated cataract in the period 2009–2014 was performed. 43 eyes underwent surgery.Results: Posterior synechiae were present in 25 eyes. Posterior synechiolysis ensured large pupil in 15 eyes, and, in 14 eyes, the use of iris hooks or pupil expansion ring was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…The technique used was the "stop and chop", the phacoemulsification device was the Legacy® 20000 and the viscoelastic used was sodium hyaluronate 3.0% -chondroitin sulfate 4.0% (Viscoat®) [40]. In addition, the positive correlation between endothelial loss and ultrasound duration, used in PE surgeries in this study, confirms the findings of other studies that point to ultrasound energy as a harmful factor to the corneal endothelium [43,[47][48][49][50][51].…”
Section: Major Findings and Discussionsupporting
confidence: 85%
“…The technique used was the "stop and chop", the phacoemulsification device was the Legacy® 20000 and the viscoelastic used was sodium hyaluronate 3.0% -chondroitin sulfate 4.0% (Viscoat®) [40]. In addition, the positive correlation between endothelial loss and ultrasound duration, used in PE surgeries in this study, confirms the findings of other studies that point to ultrasound energy as a harmful factor to the corneal endothelium [43,[47][48][49][50][51].…”
Section: Major Findings and Discussionsupporting
confidence: 85%
“…In Group 1, synechiolysis had to be performed more often during explantation surgery than in Group 2; while no synechiolysis was required in Group 3. Intraocular adhesions requiring additional manipulation carry the risk of subsequent complications [ 28 ]. Sammouh et al observed haptic migration through the iris tissue in 23% of 35 eyes treated with angle-supported (Phakic 6) pIOLs [ 29 ].…”
Section: Discussionmentioning
confidence: 99%